If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 98 + -5x = 3x + 10 Reorder the terms: 98 + -5x = 10 + 3x Solving 98 + -5x = 10 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 98 + -5x + -3x = 10 + 3x + -3x Combine like terms: -5x + -3x = -8x 98 + -8x = 10 + 3x + -3x Combine like terms: 3x + -3x = 0 98 + -8x = 10 + 0 98 + -8x = 10 Add '-98' to each side of the equation. 98 + -98 + -8x = 10 + -98 Combine like terms: 98 + -98 = 0 0 + -8x = 10 + -98 -8x = 10 + -98 Combine like terms: 10 + -98 = -88 -8x = -88 Divide each side by '-8'. x = 11 Simplifying x = 11
| 18=37-k/21 | | 4.5+0.1x=1.5 | | x^4-3x^3+4x^2-8=0 | | 7p-5(7-p)=35 | | -12+5(2s-1)=20s+3 | | 13m-6-7m-13=-23 | | 11w-3w+7w=-45 | | 60=5-(2x+9) | | 60=5(2x+9) | | 28t^2=3k-35kt | | 12(3x+5)=(10x+8) | | 2t^2+9t+4=0 | | 2x-75x^2=0 | | 0+0+0+0=24 | | 4(8-5u)=-24-4 | | 5x+16=x-20 | | 2x-5=-x-23 | | 10x+3=6x+7 | | 8x-17=-65 | | 2(y-7)=16 | | 6x+25=-x+60 | | 8(y+2)=4(2y+3)+4 | | 4(x-2)=3(x+4) | | 6x+22=16x-58 | | 3(2y+4)=6y-3 | | 45=3(2x-1) | | -5x+26=-3x+14 | | 4x+6=8x-14 | | -9x-13=-4x+32 | | (x)(2x)(4x^2)=2048 | | 10x-28=92 | | (x)(2x)(4x^2)=256 |